Children with Poor Motor Skills Have Lower Health-Related Fitness Compared to Typically Developing Children - Marisja Denysschen; Dané Coetzee; Bouwien C. M. Smits-Engelsman (MDPI AG, 2021)
Most of the current empirical evidence regarding the relationship between health-related fitness and level of motor performance is based on children from high-income countries. Yet, children from low-resource areas may have fewer opportunities to develop their fitness skills. The aim of the study was to determine if South African children from both low- and middle-income areas scoring below the 16th percentile on the Movement Assessment Battery for Children-2 (probable-Developmental Coordination Disorder (p-DCD)) have lower health-related fitness levels than typically developing (TD) children. We hypothesized that children with p-DCD would have lower overall health-related fitness than TD children. A sample of 146 participants aged 10 to 11 (10.05 years (SD = 0.41)) was collected from schools in the North West Province of South Africa, on the basis of their poverty classification. Children were tested for anaerobic capacity and strength using the Bruininks-Oseretsky test of motor proficiency second edition (BOT-2) and aerobic capacity using the Progressive Aerobic Cardiovascular Endurance Run (PACER). Body composition was evaluated using body mass index corrected for age and sex (BMI-z), body fat (BF), and waist circumference. The data was analyzed using Spearman correlations and chi-squared tests. Statistically significant differences (p < 0.05) were found between groups for running and agility, strength, and aerobic capacity. No significant differences were found between p-DCD and TD groups in terms of body mass (36.1 kg vs. 33.3 kg), waist circumference (62.2 cm vs. 59.8 cm), BMI-z (19.7 vs. 17.6), and fat percentage (20.2 vs. 18.1%). Overweight and obesity prevalence was 15% in those with low socio-economic status (SES) and 27% in high SES. In conclusion, children with p-DCD had lower muscular strength, aerobic capacity, and endurance than TD children. Although it has been reported that children with p-DCD have a higher risk for overweight/obesity than TD children, this is not (yet) the case in 10-11-year-old children living in rural areas in South Africa (North West Province).